Prebióticos e ácidos orgânicos em dietas de codornas japonesas desafiadas por Salmonella Enteritidis - Colvara, Inês Gameiro (2018)
The objective of this work was to evaluate which of the prebiotics and organic acids tested in this experiment would lead contaminated Japanese quails to reduce the excretion of Salmonella Enteritidis (SE) into the environment, thus reducing horizontal contamination without affecting egg quality or performance. To that end, 210 Japanese quail (Coturnix coturnix japonica) of 16 weeks of age were challenged with SE inoculum (1x108 UFC) and fed diets containing basal diet (T1) and diets containing possible antibiotic substitutes such as 1% beta glucan diet (T2), diet with 0,2% of MOS (t3), 2%citric acid diet (T4), 2% fumaric acid diet (T5) and diet with 0.2% of organic acid blend (T6) for 3 cycles of 21 days. They were distributed in a completely randomized design with six treatments (T1 to T6) and 5 replicates of seven birds each. The microbiological count was at 7, 21 and 35 days after inoculation (DPI), where feces and yolk samples were diluted to 1x10-6 and seeded in through XLD and SD. At the end of each cycle, variables for performance, internal and external egg quality were measured. Only at the end of the last cycle were collected duodenum, jejunum, and ileum for evaluation of intestinal morphometry as well as blood collection for two blood smears of 2 birds from each plot for counting heterophils(H), lymphocytes(L) and H/L ratio. It was observed that none of the treatments eliminated the excretion of SE in feces, however, birds receiving fumaric acid and blend of organic acids, excreted fewer bacteria (P <0.05) in both culture media at 35 DPI. However, birds fed with MOS excreted as much as the control group (P> 0.05), but with a lower immunological cost due to the absence of lymphopenia observed (P <0.05) in this treatment, indicating the success of the mechanism of action, despite no evidence of septicemia, the birds became infective by the presence of heterophils grade +4 toxicity. In performance, there was no difference (P> 0.05) for consumption / bird / day. For the production of eggs, birds that received additives, the best value (P <0.05) was observed for the use of fumaric acid compared to the worst result for MOS. The feed conversion per egg mass (g / g) and per dozen (g/dz) was better (P <0.05) for control group, fumaric acid, citric acid and blend of acids. In the egg quality, the acid blend gave heavier eggs, with a higher percentage of albumen and a better Haugh unit (P <0.05). As for the shell, the results were contradictory and unsatisfactory only for the use of citric acid. Among the additives, the acid blend increased egg weight for the same reason that fumaric acid improved egg conversion and egg production when dissociation of short-chain acids improved the digestibility of nutrients, especially amino acids. Prebiotic beta-glucan supplementation for only 9 weeks was not to eliminate the enterobacteria, however, the MOS product appears to be evocative in the excretion, but the doses for quails should be better studied so in order not to affect performance. As for intestinal morphometry, only the villus height in the duodenum differed (p <0.05) from the control group for the other treatments, indicating the recommendation of any alternative tested in this experiment. However, under the analyzed aspects of the additives in this study, it can be stated that, for a decrease and/or possible elimination of enterobacteria (SE) in the faeces of contaminated Japanese quails, it is indicated the substitution of associated organic acids or fumaric acid in order to produce eggs of better internal quality, without affecting the performance, thus satisfying the environmental, consumer and commercial needs.